Data_Sheet_1_Episodic Arctic CO2 Limitation in the West Svalbard Shelf.docx - Marina Sanz-Martín; Melissa Chierici; Elena Mesa; Paloma Carrillo-de-Albornoz; Antonio Delgado-Huertas; Susana Agustí; Marit Reigstad; Svein Kristiansen; Paul F. J. Wassmann; Carlos M. Duarte (2018)
The European Sector of the Arctic Ocean is characterized by low CO 2 concentrations in seawater during spring and summer, largely due to strong biological uptake driven by extensive plankton blooms in spring. The spring plankton bloom is eventually terminated by nutrient depletion and grazing. However, low CO 2 concentrations in seawater and low atmospheric resupply of CO 2 can cause episodes during which the phytoplankton growth is limited by CO 2 . Here, we show that gross primary production (GPP) of Arctic plankton communities increases from 32 to 72% on average with CO 2 additions in spring. Enhanced GPP with CO 2 additions occur during episodes of high productivity, low CO 2 concentration and in the presence of dissolved inorganic nutrients. However, during summer the addition of CO 2 supresses planktonic Arctic GPP. Events of CO 2 limitation in spring may contribute to the termination of the Arctic spring plankton blooms. The stimulation of GPP by CO 2 during the spring bloom provides a biotic feedback loop that might influence the global role played by the Arctic Ocean as a CO 2 sink in the future.